ANALYSIS OF FACTORS INFLUENCING MOTHER'S COMPLIANCE ON BREASTFEEDING PRACTICES ACCORDING TO WHO GUIDELINES - Wardani, Arti; Fithri, Annisa; Hidayati, Ulfa Nur; Susanti, Nanik; Winarsih, Lilik (Program Studi Sarjana Kesehatan Masyarakat Universitas Prima Indonesia, 2026)
Breastfeeding is an essential step to support the health of mothers and infants, as recommended by the World Health Organization (WHO). However, maternal adherence to breastfeeding practices according to these guidelines still faces various challenges, such as lack of understanding, social support, and health constraints. This study aims to analyze the factors that influence maternal adherence to breastfeeding practices based on WHO guidelines. The research used a descriptive analytic method with a cross-sectional design. The research sample consisted of 200 breastfeeding mothers who were selected through purposive sampling in the urban and rural areas of Malang City. Data were collected using a structured questionnaire that included variables such as maternal education level, family support, information access, and maternal health condition. Data analysis was performed using logistic regression tests to determine the relationship between these variables and the level of maternal adherence to breastfeeding practices. The results showed that maternal education level (OR = 2.35; p < 0.01) and family support (OR = 1.78; p < 0.05) had a significant relationship with breastfeeding adherence. Additionally, adequate information access and good maternal health also contributed to higher adherence levels. Factors such as education, family support, information access, and maternal health significantly influence maternal adherence to breastfeeding practices in accordance with WHO guidelines. The findings underscore the importance of comprehensive breastfeeding education programs, family involvement, and improved healthcare services to support successful breastfeeding practices.